Creditor Rights, Technology Adoption, and Productivity: Plant-Level Evidence. (26th March 2020) - Ersahin, Nuri
Abstract: I use U.S. Census microdata to analyze the effect of stronger creditor rights on productivity. Following the adoption of antirecharacterization laws that give lenders greater access to the collateral of firms in financial distress, treated plants' total factor productivity increases by 2.6%. This effect is concentrated among plants belonging to financially constrained firms. I explore the underlying mechanism and find that treated plants change the composition of their investments and their workforce toward newer capital and skilled labor. My results suggest that stronger creditor rights relax borrowing constraints and help firms adopt more efficient production technologies.